2014
DOI: 10.1155/2014/682193
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Roles of Leptin and Ghrelin in the Equine Corpus Luteum Regulation: AnIn VitroStudy

Abstract: Metabolic hormones have been associated with reproductive function modulation. Thus, the aim of this study was: (i) to characterize the immunolocalization, mRNA and protein levels of leptin (LEP), Ghrelin (GHR) and respective receptors LEPR and Ghr-R1A, throughout luteal phase; and (ii) to evaluate the role of LEP and GHR on progesterone (P4), prostaglandin (PG) E2 and PGF2α, nitric oxide (nitrite), tumor necrosis factor-α (TNF); macrophage migration inhibitory factor (MIF) secretion, and on angiogenic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…In vivo and in vitro studies in mouse ovarian explants [ 26 ] evidenced the dose-dependent effect of leptin on progesterone (P4) synthesis, with low doses stimulating and high doses inhibiting expression of enzymes involved in P4 synthesis [ 26 ]. Also, studies in other species corroborated the aforementioned observations as the in vitro treatment of equine luteal cells with lower doses of leptin supported P4 secretion, whereas higher doses presented no effect [ 27 ]. Particularly regarding follicular dynamics, studies in mice showed that high levels of circulating leptin blocked folliculogenesis, but lower circulating levels of leptin supported the transition from primary to secondary follicle [ 28 ].…”
Section: Obesity and Ovarian Functionmentioning
confidence: 60%
See 1 more Smart Citation
“…In vivo and in vitro studies in mouse ovarian explants [ 26 ] evidenced the dose-dependent effect of leptin on progesterone (P4) synthesis, with low doses stimulating and high doses inhibiting expression of enzymes involved in P4 synthesis [ 26 ]. Also, studies in other species corroborated the aforementioned observations as the in vitro treatment of equine luteal cells with lower doses of leptin supported P4 secretion, whereas higher doses presented no effect [ 27 ]. Particularly regarding follicular dynamics, studies in mice showed that high levels of circulating leptin blocked folliculogenesis, but lower circulating levels of leptin supported the transition from primary to secondary follicle [ 28 ].…”
Section: Obesity and Ovarian Functionmentioning
confidence: 60%
“…Leptin negatively affected intracellular cAMP levels, MAPK signaling, and aromatase Cyp19a1 mRNA expression with consequent downregulation of E2 synthesis [ 99 ]. Finally, we and others have also shown leptin effects on P4 synthesis, as leptin regulated, in a dose-dependent manner, the expression of cytochrome P450 side chain cleavage (P450 scc) and 3β hydroxysteroid dehydrogenase (HSD) [ 26 , 27 ]. Therefore, obesity and consequent hyperleptinemia can impair steroidogenesis in the growing antral follicle.…”
Section: Molecular Regulation Of Early Antral To Preovulatory Follicle Transitionmentioning
confidence: 99%
“…Based on gene sequences in GenBank (National Center for Biotechnology Information), the primers for Nlrp3, Casp1, Asc,Tnf ,which sequences are presented in Table 2, were designed using Primer Express 3.0 software (Applied Biosystems). All reactions were carried out in duplicates in 384-well plate (4309849; Applied Biosystems) in 12 µl of total solution volume (Galvão et al 2014). The data were analysed using the real-time PCR Miner algorithm (S. Zhao and Fernald 2005).…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Last, not least, there are several cell surface molecules and receptors relevant to angiogenesis that have been identified in equine endothelial cells—although not necessarily in studies on angiogenesis but in a different context. Examples are the immunolocalization of leptin and ghrelin in equine luteal endothelial cells in vitro (Galvao et al., 2014).…”
Section: Endothelial Regulatory Molecules In Equine Angiogenesismentioning
confidence: 99%
“…During the late luteal phase, NO and progesterone 4 inhibit angiogenesis, preparing the CL for functional and structural regression (Ferreira‐Dias & Skarzynski, 2008). Leptin and ghrelin play opposing roles during development and regression of the equine CL, with leptin promoting angiogenesis and ghrelin enhancing luteolysis (Galvao et al., 2014).…”
Section: Angiogenesis Research In Equine Reproductionmentioning
confidence: 99%